State Power on Agrarian Conflict in Nagari Air Bangis, West Sumatera - Sari, Novita; Maulana, Yoga Riski; Yanti, Siti Hardi; Faraidiany, Maghfira; Muliawati, Muliawati (Journal of Governance and Social Policy, 2025)
Agrarian conflicts in Indonesia, are deeply rooted in the tensions between customary land rights and state development projects. The enactment of Law No. 5 of 1960 and West Sumatras Regional Regulation No. 7 of 2023 aimed to address these conflicts, yet the legal framework remains inadequate. The strategic location of Nagari Air Bangis, coupled with its rich natural resources, has attracted state and corporate interests, leading to conflicts over land that has been traditionally managed by local communities for generations. This study explores the dynamics of these agrarian conflicts, focusing on the impact of national strategic projects, such as industrial developments. Despite regulations that recognize the community's rights to their customary land, these rights are often overlooked in favor of state interests, resulting in significant socio-economic implications for the local populace. The research employs a literature review. revealing that conflict resolution efforts have primarily relied on negotiation and mediation, yet often fall short. This study emphasizes the urgent need for stronger policies that balance state development goals with the preservation of indigenous rights. By highlighting the challenges faced by the Nagari Air Bangis community.